Coping style, anxiety level, organizational support, and work commitment of educators during the COVID-19 pandemic in the Philippines: A mixed-methods study - Aragasi, Norhidayah A.; Pangandaman, Hamdoni K. (Belitung Raya Foundation, Indonesia, 2021)
Background: The emergence of the COVID-19 pandemic has distorted the education system, which greatly challenged educators in the pursuit of the continuity and quality of education. Commitment to perform duties and responsibilities are bounded in coping with the situation, emotional state, and the support from the organization.Objective: To analyze and understand the presumed interrelationship of modeled variables, such as the coping style, anxiety level, organizational support, and work commitment of educators during the COVID-19 pandemic.Methods: It is a mixed-methods study through an explanatory sequential approach. The path analysis technique was applied for quantitative with 116 educators as sample respondents guided by selection criteria. Digital immigrant educators with extreme responses were identified and asked permission for an interview. Open-access adapted questionnaires used were Simplified Coping Style Questionnaire (SCSQ), Beck Anxiety Inventory (BAI), Perceived Organizational Support (POS), Allen and Meyer’s Organizational Commitment Questionnaire (OCQ). Data were processed and analyzed using SPSS and AMOS for descriptive and inferential statistics. A four-domain semi-structured questionnaire served as a guide in interviewing participants in the context of coping, anxiety, support, and work commitment. Thematic analysis was performed to generate themes. Results: This study shown that educators often used coping style (1.87 ± 0.84; Mean ± SD), have a low level of anxiety (0.58 ± 0.69; Mean ± SD), have perceived uncertainty related to organizational support (4.03 ± 1.37; Mean ± SD), and neither agree nor disagree in terms of their work commitment (3.02 ± 0.93; Mean ± SD). The presumed model through path analysis has significantly predicted 28% plausibility (R2= 0.28) with only organizational support that shown significant influence towards educators’ work commitment (β = 0.22). The themes that emerged are challenging adjustment, predestined situation, fear of getting infected, difficulty teaching effectively, technologically challenged, psychosocial assistance, uncertainty, and willingness to explore.Conclusion: Educators during the COVID-19 pandemic were able to cope and control their anxiety through the test of time, seamless work commitment, and presence of support. This study can be considered a framework for situational analysis of nurse educators in the academic realm in times of emergency and disaster.